Optimalisasi teknik counter pressure sebagai strategi nonfarmakologis dalam mengatasi nyeri persalinan kala I: Sebuah tinjauan literatur - Ni Luh Putu Mirayanti; Ni Made Dwi Mahayati; Ni Nyoman Suindri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Labor pain is a physiological process experienced by almost all women, especially during the first stage of labor due to uterine contractions and cervical dilation. Pain intensity generally ranges from moderate to severe and can affect the mother's physical and psychological well-being. Inadequate pain management can increase anxiety, prolong labor, and reduce the quality of the birth experience. Therefore, effective and safe non-pharmacological interventions are needed. One method that can be used is the counterpressure technique, which applies pressure to the sacral area to reduce pain perception. Purpose: To analyze the effectiveness of the counterpressure technique in reducing pain intensity during the first stage of labor. Method: This study used a literature review design by examining scientific articles obtained from Google Scholar, PubMed, and ScienceDirect databases. Articles were searched using the keywords